A coupling model for the cooperative actuation mechanism of thermochemically responsive shape memory polymers. (1st December 2022) - Wang, Xiaodong
Abstract: Thermochemically responsive shape memory polymers (SMPs) have attracted great interest in biomedical applications such as drug-releasing capsules and implantable medical stents, because body temperature can drive their shape recovery behaviors. However, it is difficult to determine the configurational dynamics of polymer segments due to the complexities of environmental stimuli (e.g. solute concentration, temperature change, and solvent diffusion). Besides, the cooperative actuation mechanism behind the thermochemical-driven shape memory effect (SME) is still poorly understood. In this study, we describe the effects of temperature and solvent absorption on conformational rearrangements in SMPs using the size change of cooperative rearrangement region (CRR) derived from the Adam–Gibbs model. The quasi-lattice model is further combined with Fick's second law to characterize the kinetic diffusion behavior of solvent molecules in the CRR. The dependences of dual- and quadruple-SMEs in amorphous SMPs on immersion time, solution concentration, and programming temperature are quantitatively investigated using the proposed model. The theoretical results are also compared with experimental data and a good agreement is achieved. The proposed model is expected to provide theoretical guidance for understanding the working mechanism of thermochemically responsive SMPs and advancing their engineering applications.